“The competency assessment (PTK) for effective job performance in Kuala Lumpur City Hall (DBKL)” / Farah Umaina Fajar Kareem - Fajar Kareem, Farah Umaina (Faculty of Business and Management, 2010)
Agree or not, Human Resource Department is very important in any organization. Whether an organization consists of five or 25,000 employees, human resource management is vital to the success of the organization. Aligned with that, the demand for effective and competent employees continuously increases in both public and private organization because a dynamic global marketplace and increasing foreign competition has compelled organizations to become more effective. As a result, this is a suitable time to assess human resource management practices that can augment organizational performance in public sector organizations (Gould-Williams, 2003). Kuala Lumpur City Hall (DBKL), in 1980s, one of the most important departments is the training centre and examination unit but however, they are two different entities. Its only in late of 2006, there are restructuring of Human Resource Department by combining this two units becoming one as “Bahagian Penilaian Kompetensi dan Latihan”. The objectives of existence of this department are to manage training and examination and also ensuring that every officer and staff in DBKL had the chance to sit for examination in order to be promoted for higher position. Other than that, it also ensures that every qualified staff sits for the PTK examination for the purpose of fulfilling the requirement of effective and efficient staffs in DBKL. The objectives of this research on the other hand is to investigate how the PTK examination will impacts staff and their performance after sit for the exam, the impact of the new modification and the impact on staff from the superior perspective. Researcher also found that between theories been learned and what been practice in the DBKL is not much different because the objective is still the same.